KETIDAKPADANAN DIKSI TERJEMAHAN ACHMAD SUNARTO DALAM BUKU TERJEMAH TA’LIM MUTA’ALIM - Pamungkas, Muhammad Ibnu; Musthafa, Izzuddin; Nurhasan, Muhammad (Hijai - Journal on Arabic Language and Literature, 2019)
Ta’lim Muta’alim is Syaikh al-Zarnūjī’s opus that consists of norms, ethics, and rules for gaining knowledge based on Islamic teachings. Thus, claimants of science could reach their goals to obtain it. This book was translated by Achmad Sunarto into Indonesian language and published by Husaini Publisher in Bandung. After reading it totally, researcher found mistakes in translation, especially mistakes in words selection (diction) in translation. And after analyzed it, researcher formulate the mistakes into 4 parts, (1) translation that is the result of direct transliteration from SL without considering its compability in TL, (2) existence of information loss and gain that effects the translation itself and makes it unsuitable, (3) choosing a word which is not suit with the meaning reference from the source text, (4) translation is unacceptable in TL because it is translated literally.